Next-Generation-Sequencing of the Human B-Cell Receptor Improves Detection and Diagnosis and Enhances Disease Monitoring in Patients with Gastric Mucosa-Associated Lymphoid Tissue Lymphoma - Chidimma Agatha Akpa; Cora Husemann; Chris Allen; Ann-Christin von Brünneck; Jana Ihlow; Michael Hummel (Journal of Molecular Pathology)
Mucosa-associated lymphoid tissue (MALT) lymphomas are slow-growing B-cell lymphomas mainly diagnosed in the stomach and termed gastric MALT lymphoma (G-MALT). Despite histological evaluation, immunostaining, and additional B-cell clonality analysis by fragment analysis, a clear-cut diagnosis is not feasible in all cases, especially for clinical follow-up of patients after treatment. We examined clonally rearranged immunoglobulin heavy- and light-chain gene sequences of 36 genomic DNA samples from six different patients obtained at different time points over the course of several years using the OncomineTM B-cell receptor pan-clonality next-generation sequencing (NGS) assay. Each case consisted of samples diagnosed with G-MALT and samples without evidence of lymphoma, based on histological examinations. We show a robust correlation (100%) of the results between the applied NGS method and histology-diagnosed G-MALT-positive patients. We also detected malignant clonotypes in samples where histology assessment failed to provide clear evidence of G-MALT (15 out of 19 samples). Furthermore, this method revealed malignant clonotypes much earlier in the disease course, with NGS of the immunoglobulin light chain being crucial in complementing immunoglobulin heavy-chain analysis. Hence, the value of NGS in routine lymphoma diagnostics is greatly significant and can be explored in order to provide better diagnoses and proffer the early detection of lymphoma relapse.